1976
DOI: 10.2527/jas1976.422393x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyunsaturated Fatty Acids and Vitamin E Level of the Sow Gestation Diet on Reproductive Performance and on Level of Alpha Tocopherol in Colostrum, Milk and Dam and Progeny Blood Serum

Abstract: Sixteen Yorkshire gilts were assigned randomly to four semi-purified diets fed throughout gestation and lactation. Two sources of fat (stripped lard and stripped corn oil) were fed factorially with two levels of vitamin E (atocopheryl acetate, 0 and 100 IU/kg of diet). All diets were supplemented with .05 ppm Se as Na2SeO3. Reproductive performance (litter size, individual pig birth weight, weaning weight and livability) was not affected by diet. No signs of selenium-vitamin E deficiency were noted in either d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
4
14
1
Order By: Relevance
“…This a-tocopherol was, obviously, taken from colostrum and milk, where it was drained from plasma. This explains the decreased atocopherol concentration in sows' serum on the farrowing day and confirms the observations made by Urbanova and Tulova (1975) and Malm et al (1976). The latter reported that the atocopherol concentration in colostrum could be 6-36 times greater in sows which were supplied with extra a-tocopherol during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…This a-tocopherol was, obviously, taken from colostrum and milk, where it was drained from plasma. This explains the decreased atocopherol concentration in sows' serum on the farrowing day and confirms the observations made by Urbanova and Tulova (1975) and Malm et al (1976). The latter reported that the atocopherol concentration in colostrum could be 6-36 times greater in sows which were supplied with extra a-tocopherol during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…These observations tend to agree with work of Mino and Nishino (1973) who suggested difficulty in attempting to raise fetal vitamin E by administration of tocopherol to human mothers. Maim et al (1976) observed higher serum a-tocopherol concentrations in unsuckled newborn pigs than in their dams and suggested that considerable placental transport of vitamin E occurs in the pig. Regression equations relating piglet serum E on day one to colostrum E (table 9) indicates that 67% of the variation in piglet serum E is related to the variation in colostrum E.…”
Section: Resultsmentioning
confidence: 92%
“…A trend existed for a larger litter size in the supplemented groups but a definitive conclusion could not be made because of the small number of sows used per treatment (n = 4) [57]. Other authors showed a similar a lack of response in litter size and weight to dietary vitamin E supplementation over one parity [27,58].…”
Section: Vitamin E and Reproductive Performancementioning
confidence: 93%
“…It is known that immediately after birth, the vitamin E content in the serum is increased after suckling colostrum and milk, but there is little evidence concerning the placental transfer of vitamin E which could determine the vitamin E status of the newborn. It has been reported that the concentration of serum α-tocopherol in unsuckled newborn piglets is several fold higher than that of their dams, strongly suggesting an efficient placental transfer of vitamin E even when the dams are not supplemented with the vitamin [57]. However, most reports have suggested that, prior to nursing, the α-tocopherol concentration in the serum of neonatal piglets is low whether or not the dam is provided with adequate or supplemented dietary levels of vitamin E during gestation [30,[61][62][63][64].…”
Section: Placental Transfer Of Vitamin Ementioning
confidence: 99%